A government by the people : direct democracy in America, 1890-1940 - Goebel, Thomas, 1964- (University of North Carolina Press, 2002)
Between 1898 and 1918, many US states introduced the initiative, referendum and recall, known as direct democracy. Most interpreters have seen the motives for these reforms as purely political, but this study demonstrates that the call for direct democracy was rooted in antimonopoly sentiment.